Undersea cables and landing stations around Africa: Policy and regulatory issues - Ewan Sutherland (International Telecommunications Society (ITS), 2014)
The availability of undersea cables around Africa has been transformed by a recent surge of investment, ending the monopoly in West Africa and an absence in East Africa. Private investors alone and with governments have funded the laying of cables. Consequently, previous calls for regulated access are no longer appropriate, with the need for more detailed analysis of remaining bottlenecks to ensure affordable prices in telephony and Internet access.
Keywords: 330; Africa; Governance; Policy; Regulation; Submarine; Telecommunications